The Utilization of Education Report Cards as a Basis for Data-Driven Planning in Strengthening Student Character - Menuk Rahmawati; Basukiyatno Basukiyatno; Suriswo Suriswo (Research Horizon, 2026)
This research is driven by the necessity of enhancing character education in schools, which continues to encounter implementation challenges, along with the inadequate utilization of the education report card as a data-driven tool for planning character initiatives. This study aims to examine the use of the education report card in assessing and designing programs for character development, the strategies adopted by schools, and the obstacles faced in public senior high schools in Pemalang Regency. This study utilized a qualitative method featuring a multisite case study design that included three public senior high schools and involved 15 participants, comprising principals, teachers, students, and representatives from the school committee. Data were gathered via interviews, observations, and documentation, and thematically analyzed using NVivo software. The results indicate that the education report card serves as a foundation for assessing students’ character conditions and devising programs via school work plans and annual work plans. This is executed through cooperative curricular learning, religious and environmental practices, enhancement of literacy and numeracy, teacher role modeling, and counseling services. Nonetheless, execution remains hindered by insufficient teacher data literacy, poor coordination, and inadequate monitoring and evaluation systems.